Best practices and factors to enhance transfer of training in Oman - Al Ghafri, Ahmed Mohammed Issa (2014)
Increasing investments are devoted to human resources development in Oman. Training is an essential component of these investments. This study aims to explore the perceptions of trainers on the best practices to enhance the transfer of training. The study was guided by three main questions: (1) How can we best enhance transfer in Oman, (2) what does affect transfer of training in Oman, (3) who should be involved in the process of training transfer. Using Swanson and Holton‟s (2001) and Baldwin and Ford‟s (1988) models of the transfer of training, the study explores the transfer of training from a systemic and multidimensional perspective that represents the challenge of the transfer of training to performance (Burke and Hutchins, 2007). The current study employs the qualitative approach to provide answers to the research questions. Semi-structured interviews were used to investigate the views of the participants on the research problem, based on their experiences in the training field. The technique of semi-structured interviews allowed to get in-depth information on the trainers‟ opinions and, hence, to provide answers to the research questions. Moreover, the gathered data were analyzed qualitatively to suggest the most effective practices (best practices) that should be integrated in the training interventions. The study participants indicated that trainees‟ involvement, setting clear objectives, linking training outcomes to the workplace performance, supervisory support, evaluation assignments, post-training discussions, peers training, having supportive work climate, and performance observation as the best practices that enhance the transfer of training in Oman. Moreover, the participants reported some factors that affect training transfer to the workplace, such as expectations, trainees‟ characteristics, supervisor‟s or manager‟s attitude towards training, and work environment. They also determined a list of stakeholders, whom are able to support or hinder the transfer of training. The list includes training designers, trainers, supervisor, managers, peers, top management, and customers or clients of the organizations. To my knowledge, this could be the first study conducted on the issue of the transfer of training in the Omani context. The conclusions drawn from this study may guide the training managers and planners to take the proper procedures in order to boost the training effectiveness and deliver the required results in the workplace. The study may also support the efforts of the training professionals in Oman to uncover the weaknesses in the training process that may hinder the positive impact of training on the work environment.